Effects of Hydroxyl Radical Induced-Injury in Atrial Versus Ventricular Myocardium of Dog and Rabbit - Hiranandani, Nitisha; Billman, George E.; Janssen, Paul M. (Frontiers in Physiology, 2010)
Aim: Despite the widespread use of ventricular tissue in the investigation involving hydroxyl-radical (OH*) injury, one of the most potent mediators in ischemia-reperfusion injury, little is known about the impact on atrial myocardium. In this study we thus compared the OH*-induced injury response between atrial and right ventricular muscles from both rabbits and dogs under identical experimental conditions. Methods: Small, contracting ventricular and atrial rabbit and dog trabeculae were directly exposed to OH*, and contractile properties were examined and quantified. Results: A brief OH* exposure led to transient rigor like contracture with marked elevation of diastolic tension and depression of developed force. Although the injury response showed similarities between atrial and ventricular myocardium, there were significant differences as well. In rabbit atrial muscles, the development of the contracture and its peak was much faster as compared to ventricular muscles. Also, at the peak of contracture, both rabbit and dog atrial muscles show a lesser degree of contractile dysfunction. Conclusion: These results indicate that both atrial and ventricular muscles develop a rigor like contracture after acute OH*-induced injury, and atrial muscles showed a lesser degree of contractile dysfunction. Comparison of dog versus rabbit tissue shows that the response was similar in magnitude, but slower to develop in dog tissue.